Iciliidae - Lowry, J. K.; Hughes, L. E. (Zootaxa, 2009)
One species of iciliid amphipod, Icilius caledoniana Watson, Lowry & Steinberg, 2004, is reported from the northern Great Barrier Reef, Queensland, Australia, living on the calcareous green alga, Halimeda sp.